تأثير السلسلة الألكيلية في 2- و 4-ألكيل فينول على تفاعلات اصطناع الايتوكسيلات (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2018)
تم إجراء تفاعل اصطناع ايتوكسيلات متيل فينول من تفاعل تماثر اكسيد الايتيلين مع بارا -  متيل فينول ثم مع اورتو – متيل فينول باستخدام وسيط غير تقليدي هو كبريتات المغنيزيوم و هيدروكسيد الكالسيوم وذلك من أجل دراسة تأثير موضع السلسلة الألكيلية في الحلقة العطرية على تفاعل اصطناع ايتوكسيلات ألكيل الفينول وعلى درجة تجانس المنتج ومردود التفاعل. أدت عملية الاصطناع إلى الحصول على ايتوكسيل بارا متيل فينول وايتوكسيل اورتو متيل فينول وقد تم تحليل النواتج باستخدام تقنية الكروماتوغرافيا الغازية وقد تبين أن ناتج التفاعل بارا كان أكثر تجانساً لأن  المتماثرات تتوزع ضمن مجال ضيق كما أن مردود التفاعل للمتماثر الأساسي أكبر منه في حالة المنتج الثاني اورتو حيث تتوزع المتماثرات ضمن مجال أوسع مما يجعل المنتج أقل تجانساً كما أن مردود التفاعل من المتماثر الأساسي يكون منخفضاً نسبياً. The synthesis reaction of Ethoxylatephenol was achieved by polymerization reaction of Ethylene oxide with para-methylphenol or orto-methyl phenol, using Magnesium sulfate and Calcium hydroxide as non traditional catalyzer. The aim is to study the effect of Alkyl chain position in aromatic cycle on the synthesis reaction of Ethoxylate Alkyl phenol, homogeneity, and the reaction rate of product. The synthesis process led to obtaining Ethoxyl para-methyl phenol and Ehtoxyl orto-methyl phenol. The products were analyzed by gas chromatography. Results showed that the produced product para was more of a homogene than orto product, because the para polymers were distributed in a narrow range and the reaction rate of polymerization for the principal polymer was greater than the second one (orto-product). Polymers were distributed in a wide range that makes the product less homogene and the reaction rate for principal polymer relatively low.